(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Data is the basic building block of any organization. Be it an individual or an organization of any type, it is surrounded by huge flow of quantitative or qualitative data. Data are the patterns which are used to develop or enhance information or knowledge. All the organizations big or small have bulk of data which needs to be stored or retrieved systematically to form information. The repository of data is known as Database. With the advancement in computer science, the database has taken many shapes. According to the applications, starting from the traditional file system to hierarchical, network, relational, object oriented, associative, now it has reached to data warehouses and data marts, etc.